BLOCKCHAIN MARKET: REGULATORY CONCERNS ARISING FROM THE ‘DIEM’ EXAMPLE IN THE FIELD OF FREE COMPETITION (EU and comparative law issues and challenges series (ECLIC), 2021)
The purpose of this paper is to shed light on competition law issues arising from the extensive use of the blockchain technology. By using the example of the Diem, which has also aroused the interest of the European regulators, the author will try to illustrate the issues that the competent competition authorities will immediately have to deal with. These preliminary questions relate mainly to the re-definition of the concept of an ‘undertaking’ under the new circumstances and the attempt to define the relevant market on the basis of the existing theories. Indeed, legal scientists and economists have succeeded in highlighting the predominant theories for defining the relevant market in the blockchain environment. This study aims to support this vivid theoretical dialogue by suggesting an holistic theory which compromises all those previously expressed elements. In conclusion, this paper intends to investigate whether these new circumstances are endangering the very existence of competition law itself. The latter, in order to continue to fulfil its aim effectively, is probably very close to radical reforms, even in its most fundamental pillars.